2015
DOI: 10.1021/cb501020r
|View full text |Cite
|
Sign up to set email alerts
|

Hydrocarbon Stapled Peptides as Modulators of Biological Function

Abstract: Peptide-based drug discovery has experienced a significant upturn within the past decade since the introduction of chemical modifications and unnatural amino acids has allowed for overcoming some of the drawbacks associated with peptide therapeutics. Strengthened by such features, modified peptides become capable of occupying a niche that emerges between the two major classes of today's therapeutics-small molecules (<500 Da) and biologics (>5000 Da). Stabilized α-helices have proven particularly successful at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
238
0
8

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 267 publications
(249 citation statements)
references
References 166 publications
3
238
0
8
Order By: Relevance
“…Since then, a range of studies has demonstrated the potential utility of hydrocarbon stapled peptides in the treatment of various human diseases. Two hydrocarbon stapled peptides have reached clinical trials, epitomising the remarkable progress made in this field within the past 15 years [49]. A paradigm for stapled peptide design is also gradually being developed based on the huge body of experimental data that has been collected so far.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since then, a range of studies has demonstrated the potential utility of hydrocarbon stapled peptides in the treatment of various human diseases. Two hydrocarbon stapled peptides have reached clinical trials, epitomising the remarkable progress made in this field within the past 15 years [49]. A paradigm for stapled peptide design is also gradually being developed based on the huge body of experimental data that has been collected so far.…”
Section: Discussionmentioning
confidence: 99%
“…They have also shown potential as therapeutic agents for various other diseases, such as HIV [44,45], diabetes [46], cardiovascular disease [47], and respiratory infection [48]. Two hydrocarbon-stapled peptides developed by Aileron Therapeutics are currently undergoing clinical trials for the treatment of orphan endocrine disorders and malignant tumours [49].…”
Section: Hydrocarbon Staplesmentioning
confidence: 99%
“…[80,81] Stabilized a-helices have proven highly successful in inhibiting protein-protein interactions (PPIs), with hydrogen-bond surrogates (HBS) and stapled peptides resembling the most advanced approaches within that field. [83,84] HBS3 (10)isaderivative of aHwith enhanced solubility and was designed as an inhibitor of the Ras-SOS interaction ( Figure 6b). It shows moderate affinity for GDPbound (K d = 158 mm)a sw ell as nucleotide-free (nf) H-Ras (K d = 28 mm).…”
Section: T N Grossmann H Waldmann Et Almentioning
confidence: 99%
“…[136] Peptide stapling [84] can be used to stabilize the a-helical conformation of ag iven peptide by introduction of an all-hydrocarbon macrocyclic bridge to interconnect two turns of ah elix. In af irst step,c omplexes of Rab proteins with various interaction partners were analyzed with respect to their interaction surface to identify suitable a-helical binding domains.T he top-rated peptide fragments were tested with arepresentative set of six different Rab proteins in all nucleotide binding states to yield four peptides which bind nucleotide-free Rab proteins in the low micromolar range.I ncorporation of hydrocarbon staples into these peptide sequences produced alibrary of stapled peptides which bind arepresentative set of Rab proteins in the nucleotide-free form with varying selectivity and affinity down to the submicromolar range.…”
Section: Peptide-based Rab Inhibitorsmentioning
confidence: 99%
“…Peptidomimetics have found numerous applications in the fields of drug designing, drug delivery, synthetic hormones, growth factors and many other such aspects of health care where physiology encounters its limits [19][20] .…”
mentioning
confidence: 99%